Indeks Pembangunan Manusia Ilmu Pengetahuan - Yeni Yulianti; Siti Qomariah (Lembaga Pengembangan Kinerja Dosen, 2025)
The Human Development Index (HDI) is a critical indicator that measures the quality of development in a region through health, education, and economic dimensions. This study aims to analyze the key factors influencing HDI and its impact on social development in Indonesia. Using a descriptive analysis approach, secondary data from Statistics Indonesia (BPS) were utilized to evaluate HDI trends and disparities in recent years. Findings indicate that HDI improvement directly impacts community welfare, strengthens social stability, and reduces economic inequality. However, challenges such as regional disparities and unequal access to basic services must be addressed to achieve sustainable development. The implications of this study are expected to serve as a reference for policymakers in designing more inclusive development strategies.